The Use of Flashcard to Teach Speaking at the Second Year Students of MA Yafallah - Etika Dewi Kusumaningtyas (Journalistics: Journal of English Teaching and Applied Linguistics, 2021)
This research applied quasi-experimental method with two groups pre-test and posttest design. There were two variables of this research; they were independent variable and dependent variable, while the independent variable was Flashcard and dependent variable was students’ speaking skill. The population of this research was the second years students of MA Yafallah year 2020 consisting of 352 students. The sample of the research consisted of 60 students which were taken by using Purposive Sampling technique.This reasearch used only one instrument. That was the oral speaking test. Futhermore, that instrument process was used pre-test and post-test. Moreover, the researcher collected the data with assessing student’s vocabulary and fluency. As the result, the data indicated that there was significant differences between students post-test in experimental class and control class. The mean score of post-test (4.1) in experimental class was greater than the mean score of post-test (2.9) in controlled class. From t-test, the researcher found that the value of t-test (2.29) was greater than t-table (2.00). Therefore, the researcher suggested that The Use of Flashcard is effective in teaching speaking